Spectrum and Bethe-Salpeter amplitudes of Ω baryons from lattice QCD - 梁剑 孙玮 陈莹 邱伟峰 宫明 刘川 刘玉斌 刘朝峰 马建平 张剑波 (Chinese physics C, 2016)
The Ω baryons with JP= 3/2^±, 1/2^± are studied on the lattice in the quenched approximation. Their mass levels are ordered as M3/2＋〈 M3/2- 0≈M1/2-〈 M1/2＋, as is expected from the constituent quark model. The mass values are also close to those of the four Ωstates observed in experiments. We calculate the Bethe-Salpeter amplitudes of Ω（3/2^＋） and Ω（1/2^＋） and find there is a radial node for the Ω（1/2＋） Bethe-Salpeter amplitude, which may imply that Ω（1/2＋） is an orbital excitation of Ω baryons as a member of the（D, LN^P） =（70, 02^＋） supermultiplet in the SU（6）×O（3） quark model description. Our results are helpful for identifying the quantum numbers of experimentally observed Ω states.